Spinal cord ischemia in endovascular repair of thoracoabdominal and complex abdominal aortic aneurysm: a single-center cohort study - Magalhães,Tiago (2024)
Abstract Introduction: Spinal cord ischemia (SCI) is an uncommon but one of the most terrifying complications associated with the treatment of extensive aortic aneurysms. Its pathophysiology, risk factors, and event characteristics must be clarified. This study aimed to perform a descriptive analysis of the cases of SCI after complex aortic repair at our center and to understand which factors contributed to the event. Methods: A retrospective, single-center, cohort study of prospectively collected data was performed. From January 2013 to October 2022, we included all consecutive patients with thoraco-abdominal aneurysms (TAAA) and complex abdominal aneurysms submitted to an endovascular procedure using fenestrated or branched endografts. According to the Society for Vascular Surgery (SVS) reporting standards, SCI was defined as the development of new motor or sensitive deficits after endovascular treatment. Results: One hundred and thirty-five patients (87% male) were included, with a median age of 72. A total of 53,7% (n=72) had thoraco-abdominal aneurysms (type I-V), of which 63 were extent I-III\V and 9 were extent IV. In total, 12 (9%) SCI events were identified; 7 patients had a grade 2 SCI, 5 had a grade 3 injury, and all of them had a TAAA. Of these, 10 had pre-procedure cerebrospinal fluid (CSF) drainage. Five (42%) developed symptoms after 48 hours (delayed SCI), and seven patients developed early SCI, being identified on the first evaluation after surgery. Five cases received rescue CSF drainage (after the beginning of symptoms), with some degree of improvement observed in all cases. Among patients with grade 2 SCI (n=7), five recovered completely, one recovered partially (maintaining sensitive symptoms - grade 1), and one did not recover. This corresponded to an overall incidence of permanent SCI of 5.2% (n=7, any grade) and 1.5% of permanent paraplegia (n=2, grade 3, 2.8% only in TAAA). Conclusion: In this study, SCI only occurred in patients with TAAA, and the incidence of permanent paraplegia in this group was 2,8%. In five patients, rescue CSF drainage was applied, with some degree of clinical improvement. The small number of events precluded the investigation of predictors. Notably, 42% of SCI cases happened after 48 hours, showing a high prevalence of delayed SCI in this population. Consequently, more extended monitoring of these patients should be considered.